Optimization of water distribution network by genetic algorithm with EPANET-Python Toolkit - Pavansimha, M N; Yusuf Javeed (Journal of Earth System Science, 2025)
Water distribution systems (WDS) are essential for supplying water to urban and rural areas in an effective and consistent manner. This WDS operation may have a substantial effect on the environment and the sustainable development of cities in the future because of the substantial quantity of energy that WDSs consume over the course of their lives. To improve the quality of life and to maintain the sustainability of nature, optimization of the water distribution network (WDN) is essential and also crucial to guarantee the accessibility of safe drinking water to homes, businesses, industries, and public facilities. To provide optimal or nearly optimal solutions for large-scale and complicated WDS networks, the genetic algorithm (GA) is used to efficiently search across the enormous solution space. The optimization of pipe diameter is obtained with respect to total network cost by combining GA with the EPANET-Python Toolkit for the Benchmark Network (Hanoi Network) which is for validation purpose and later Real-world Network (Koodlahalli Network) which is made of High-Density Polyethylene (HDPE) pipe and cost of pipes in the network is reduced from Rs. 775989.42 to Rs. 690540.27, around (11%) has been reduced with minimum pressure of 7 m.